(untitled) (Revista de Psicología, 2025)
During the pandemic, the use of technology accelerated the development of e-government, although its adoption has been uneven. Gamification (i.e., the incorporation of game elements) in e-government could facilitate its adoption, a topic that has been scarcely studied in Argentina. This study examines the perceived importance of gamification components in e-government, as well as perceived enjoyment, motivation, innovation, and their relationship with sociodemographic variables such as age, gender, education level, and socioeconomic status. A total of 211 individuals participated (Mage = 33.47; 78.20% women; 59.24% with secondary education; 47.9% with middle-upper socioeconomic status). Results showed that 70.20% considered it important to include gamification components in e government, with progress bars rated most important (78.10%). While about half perceived these components as enjoyable and innovative, only 39% found them motivating. Higher age, education, and socioeconomic status were associated with lower perceived importance, enjoyment, motivation, and innovation, with no significant gender differences. These findings are essential to inform strategies that foster e-government adoption in Argentina.